From Texts to Technology: Employing Content-Based Instruction Approach to Enhance Reading Proficiency and Environmental Consciousness in ESL Engineering Students - D., Praveen Sam; S., Keerthy (Journal of Engineering Education Transformations, 2025)
Engineering is one of India’s most preferred genres in higher education. Technical English language courses are offered to Engineering students in the first and second semesters. The primary objectives of these courses are to prepare learners to handle technical subjects, most of the time discoursed using the English language and to use the language skills appropriately in authentic contexts. Reading is one of the important skills focused on during these courses. This work concentrates on the impact of content related to environmental consciousness as materials for reading instruction on tertiary-level engineering learners in the English as a Second Language (ESL) context. Further, the samples were investigated using a one-group-pretest-post-test design. The t-test for two means was used to statistically analyse the data collected during the survey and the results of the pretest and post-test. As a part of the study, a survey on the impact of Content-based Instruction (CBI) was conducted, and the survey reflected the effectiveness of the content on the environment in developing reading competence as well as a medium in realising the importance of environmental consciousness. The survey was performed using a semi-structured interview, and four learner variables were identified, namely- Prior Knowledge, Interest in Environmental Issues, Learning Style, Personal Beliefs and Values This paper presents the pedagogical implications of using content related to the environment and the impact of these materials on learners. This content has been used to improve reading comprehension skills and create awareness of the responsibilities of budding engineers towards the environment.